O uso das fractais e multifractais na analise geografica - Christofoletti, A. L H [UNESP]; Christofoletti, A. [UNESP] (My University, 1998)
The fractal and multifractal approaches in the geographical analysis. This paper results from a bibliographical research showing the applications of the fractal and multifractal approaches in the geographical studies. At first describes some text books about fractals and, after, focuses the works did concerned with Physical Geography, Meteorology, Climatology, Geomorphology, Pedology and Human Geography.
The use of fractal and multifractal approaches in geographical analysis
Keywords: Fractals; Geographical analysis; Multifractals; climatology; fractal analysis; geomorphology; meteorology; pedology